2015
DOI: 10.1111/sed.12215
|View full text |Cite
|
Sign up to set email alerts
|

Depositional controls on mixed carbonate–siliciclastic cycles and sequences on gently inclined shelf profiles

Abstract: The interplay between carbonate production and siliciclastic input produces mixed systems that typically contain a very high degree of lateral and vertical facies heterogeneity. This heterogeneity complicates the sequence stratigraphic analysis of mixed systems. Outcrop studies facilitate the deciphering of controls and understanding of facies distributions within sedimentary successions. The Picún Leufú Anticline in the Neuquén Basin (Argentina) offers the opportunity to integrate large‐scale depositional arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 55 publications
2
77
0
5
Order By: Relevance
“…Consistent with the results of the present study, the discriminating factor dividing the Neuquén dataset of Zeller et al (2015aZeller et al ( , 2015b was mineralogy (lithological variation). The petrophysical properties of carbonates, sandstones and shales occupy slightly overlapping domains in a P-wave velocity versus porosity cross-plot with low porosities (which had a small range) and high acoustic velocities for carbonates, an intermediate spread in acoustic velocities and porosities for sandstones, and low velocities and variable porosities for shales (see Fig.…”
Section: Comparison With Other Mixed Carbonate and Non-carbonate Deposupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with the results of the present study, the discriminating factor dividing the Neuquén dataset of Zeller et al (2015aZeller et al ( , 2015b was mineralogy (lithological variation). The petrophysical properties of carbonates, sandstones and shales occupy slightly overlapping domains in a P-wave velocity versus porosity cross-plot with low porosities (which had a small range) and high acoustic velocities for carbonates, an intermediate spread in acoustic velocities and porosities for sandstones, and low velocities and variable porosities for shales (see Fig.…”
Section: Comparison With Other Mixed Carbonate and Non-carbonate Deposupporting
confidence: 91%
“…Braaksma et al (2003Braaksma et al ( , 2006) studied a Jurassic ramp system (Boulonnais, northern France) including coastal plain sand-and mudstones, shallow-marine sandstones and shelf mudstones, and found that the acoustic properties of the sediments were mainly controlled by porosity and to a lesser extent by carbonate or clay content. Zeller et al (2015aZeller et al ( , 2015b distinguished three lithological groups (carbonates, sandstones and shales) in a mixed shelf succession in the Neuquén Basin (Argentina). These lithologies had different petrophysical signatures which were used for synthetic seismic modelling.…”
Section: Comparison With Other Mixed Carbonate and Non-carbonate Depomentioning
confidence: 99%
“…The carbonate sediments of the dolomite lithofacies were deposited in a shallow, restricted lagoon environment, dolomarl (shallow marine sediments, where the enhanced terrigenous input was the results of the more humid climate), reddish silty claystone (paleosol) and sandstone (terrigenous provenance) indicating that the sediments of the Construction site were formed in inner ramp lagoon and related tidal flat environments. The alternation of siliciclast rich and carbonate rich sediments can be frequently interpreted as the results of short-term sealevel or climate changes (e.g., Wilson 1967;Brachert et al 2003;Colombié et al 2012;Caracciolo et al 2013;Zeller et al 2015;Blanchard et al 2016;Reis & Suss 2016;Chiarella et al 2017). The short-term sea-level changes have a significant control on the sedimentation of the shallow marine environment, because during the lowstands, carbonate sediment GEOLOGICA CARPATHICA, 2019, 70, 2, 135-152 production is slowed down or halted and the terrigenous influx can increase, resulting in the predominance of siliciclast deposition (Wilson 1967;Brachert et al 2003;Carcel et al 2010;Caracciolo et al 2013;Chiarella et al 2017 and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…The alternation of lithofacies and/or the sediment mixing can be interpreted as the result of short-term sea-level or short-term climate changes. Thus, the investigation of this type of successions is useful to understand short-term sea-level and climatic changes and processes (e.g., Brachert et al 2003;Zeller et al 2015;Blanchard et al 2016;Reis & Suss 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic nature of sedimentary basins and carbonate sediments influenced by siliciclastic deposits have to be carefully considered are especially important for creating meaningful paleogeographic reconstructions. According to Zeller et al (2015), a mixing of carbonate production and siliciclastic input causes variable sedimentation conditions and a high degree of lateral and vertical facies heterogeneity. Generally, carbonate facies development is triggered by the requirements of the carbonate-secreting biota, which are controlled by temperature, salinity, sealevel change, input of siliciclastic sediments, and nutrients (Sanders and Höfling 2000).…”
Section: Discussionmentioning
confidence: 99%